The Effect of Guided Inquiry Learning Model on Critical Thinking Skills and Science Learning Outcomes of Elementary School Students - Musyawwir, Muh; Kune, Syarifuddin; Rahmawati, Rahmawati (Pedagogik Journal of Islamic Elementary School, 2023)
This study aims to analyze the effect of the Guided Inquiry learning model on students' critical thinking skills and science learning outcomes. The type of research used is quasi-experimental research with nonequivalent control group design. The sampling technique is a saturated sample, namely fifth grade students of public elementary school 9 West Bangkala, Jeneponto Regency, totaling 56 students. Research data were analyzed through descriptive analysis and inferential analysis using SPSS 22. Based on the results of the study it can be concluded that the use of guided inquiry learning models can improve critical thinking skills and student learning outcomes compared to those without using the guided inquiry learning model. The results of the study using the inquiry learning model had an effect on critical thinking skills and science learning outcomes for fifth grade students of public elementary school 9 Bangkala Barat, Jeneponto Regency.